2017
DOI: 10.1103/physrevb.95.045138
|View full text |Cite
|
Sign up to set email alerts
|

Image-potential-induced spin-orbit interaction in one-dimensional electron systems

Abstract: We study the spin-orbit interaction effects in a one-dimensional electron system that result from the image charges in a nearby metallic gate. The nontrivial property of the image-potential-induced spin-orbit interaction (iSOI) is that it directly depends on the electron density because of which a positive feedback arises between the electron density and the iSOI magnitude. As a result, the system becomes unstable against the density fluctuations under certain conditions. In addition, the iSOI contributes to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…In particular, InAs and InSb nanowires are promising systems for the creation of helical states and as a host for Majorana fermions [11][12][13]. The fundamental reason behind these properties is the strong Rashba spin-orbit interaction (RSOI) in these materials [14].Recently we have found that RSOI is created by the electric field of the image charges that electrons induce on a nearby gate [15]. A sufficiently strong image-potential-induced spinorbit interaction (iSOI) leads to highly non-trivial effects such as the collective mode softening and subsequent loss of stability of the elementary excitations, which appear because of a positive feedback between the density of electrons and the iSOI magnitude.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, InAs and InSb nanowires are promising systems for the creation of helical states and as a host for Majorana fermions [11][12][13]. The fundamental reason behind these properties is the strong Rashba spin-orbit interaction (RSOI) in these materials [14].Recently we have found that RSOI is created by the electric field of the image charges that electrons induce on a nearby gate [15]. A sufficiently strong image-potential-induced spinorbit interaction (iSOI) leads to highly non-trivial effects such as the collective mode softening and subsequent loss of stability of the elementary excitations, which appear because of a positive feedback between the density of electrons and the iSOI magnitude.…”
mentioning
confidence: 99%
“…Recently we have found that RSOI is created by the electric field of the image charges that electrons induce on a nearby gate [15]. A sufficiently strong image-potential-induced spinorbit interaction (iSOI) leads to highly non-trivial effects such as the collective mode softening and subsequent loss of stability of the elementary excitations, which appear because of a positive feedback between the density of electrons and the iSOI magnitude.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The iSOI not only breaks the SCS, but also leads the system to the instability for sufficiently strong interaction. [4] The SCS can also be violated in 1D edge states of two-dimensional topological insulators. These states are known to have a helical structure with the spin locked to the electron momentum.…”
mentioning
confidence: 99%